Simple model for predicting hourly air temperatures inside Chinese solar greenhouses - Dong, Qiaoxue; Liu, Jiechang; Qu, Mei (International Journal of Agricultural and Biological Engineering, 2023)
For an efficient energy greenhouse, temperature is the most important climate parameter, which not only affects cropgrowth and health but also determines the management of energy consumption. So reliable monitoring of temperature is ofgreat significance, and often hourly values are required. However, due to the low level of automation for Chinese solargreenhouse, the loss or poor quality of climate data often occurs. In order to accurately supplement the missing data, as well asfor the generation of future temperature, a 24-hour indoor temperature prediction model was established. It uses a piecewiseBezier curve equation that takes the characteristic temperature as the control point which was determined by the outsideweather recording. The 130 d of observed hourly temperature data were used to build and validate the model, and the resultsshowed that the temperature model proposed was accurate and sufficient for the simulation of the trend curve of hourlytemperature change inside a solar greenhouse. (EF=0.98, R2=0.89). After validation, this temperature model proposed can beuseful for the quantitative analysis of crop growth and optimal management.Keywords: solar greenhouse, hourly temperature, prediction model, Bezier curve equationDOI: 10.25165/j.ijabe.20231605.6922Citation: Dong Q X, Liu J C, Qu M. Simple model for predicting hourly air temperatures inside Chinese solar greenhouses.Int J Agric & Biol Eng, 2023; 16(5): 56–60.